Performance of defatted black soldier fly pre-pupae meal as fishmeal replacement in the diet of lemon fin barb hybrid fingerlings - Kamarudin, Mohd Salleh; Rosle, Suharmili; Md Yasin, Ina Salwany (Elsevier BV, 2021)
This study was conducted to determine the optimal level of defatted black soldier fly pre-pupae (BSFP), Hermetia illucens as a fishmeal replacement in lemon fin barb hybrid diet. Triplicate groups of fish (1.52 ± 0.01 g) were fed twice a day until apparent satiation with five iso-nitrogenous (30 %) and isocaloric (17 kJ g−1) diets containing varying BSFP levels ranging from 0 to 100 % for 8 weeks. No mortality was found during this study. BSFP level used in the diets were significantly affected the growth response of the barb hybrid. The growth performance of fish such as body weight gain and specific growth rate improved up to 75 % BSFP and decreased above this level, while feed conversion ratio and daily feed intake were not affected by BSFP levels. Body protein and lipid contents of the barb hybrid were significantly affected by dietary replacement levels. The protein retention decreased and lipid retention increased when the BSFP level increased, while the carbohydrate retention was extremely low. The most abundant of essential amino acids in the whole body of lemon fin barb hybrid was valine while glutamic acid was the abundant non-essential amino acids. No pathological changes were observed among all dietary fed groups. The present study suggested that fishmeal could be replaced up to 75 % or 2.5 % fishmeal was still required in the lemon fin barb hybrid diet.